2023
DOI: 10.2188/jea.je20210220
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific Relationship Between Stress Coping Strategies and All-cause Mortality: Japan Multi-Institutional Collaborative Cohort Study

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…It is suggested that men are psychologically distressed. Cultural and social environments are different among males and females (e.g., life events, gender role norms at home, job positions, and/or salary gaps) [19]. Male stress responses may predominantly involve the traditional "fight and flight" reaction, whereas female stress responses may be better characterized by "tend and befriend", involving nurturing activities and the creation of social networks [18].…”
Section: Gender Difference Of Ghq-30mentioning
confidence: 99%
See 4 more Smart Citations
“…It is suggested that men are psychologically distressed. Cultural and social environments are different among males and females (e.g., life events, gender role norms at home, job positions, and/or salary gaps) [19]. Male stress responses may predominantly involve the traditional "fight and flight" reaction, whereas female stress responses may be better characterized by "tend and befriend", involving nurturing activities and the creation of social networks [18].…”
Section: Gender Difference Of Ghq-30mentioning
confidence: 99%
“…In addition, women have various coping strategies and use them more frequently than men [34]. Women reportedly tend to focus on emotional coping [19] and mobilize greater social support during periods of stress [34]. In contrast, men prefer coping styles that can be practiced by themselves rather than relying on others.…”
Section: Gender Difference Of Ghq-30mentioning
confidence: 99%
See 3 more Smart Citations